Managing the brand art gallery: art visualization and overall evaluation. - Loureiro, S. M. C.; F. Lima (Proceeding of 2016 GAMMA-Global Marketing Conference -Bridging Asia and the World: Global Platform for interface between Marketing and Management, 2016)
This research was conducted in simulated art scenarios to explore the effects of three treatment variations of music on the visualization of art (not only its presence/absence was tested, but also its fast/slow perceived rhythm) and it employed a sample of 234 potential art consumers. Findings suggest that music is not able of enhancing the art experience. Actually, the study found empirical evidences of its negative influence on consumers’ emotional, cognitive and behavioral responses.